Tingkat Kesesuaian Jurusan dan Tantangan dalam Proses Belajar di Perkuliahan - Elsa Simanjuntak; Nuri Pasaribu; Norlyn Pakpahan; Monica Simorangkir; Sitti Subaedah (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study examines the extent to which the compatibility between a student's major and their interests affects their learning experience at Universitas Negeri Medan (UNIMED), particularly in the Accounting Department. The findings indicate that many students feel that their major aligns with their interests, which in turn boosts their enthusiasm for learning. However, some students choose their major due to parental pressure or promising job prospects, which ultimately leads to difficulties in their studies. Additionally, students face various challenges in the learning process, ranging from heavy academic workloads, difficulties in understanding certain subjects, to the pressure of managing time between classes and other activities. These challenges are exacerbated by the demands of mastering accounting technology and adapting to an Outcome-Based Education system. To overcome these obstacles, students employ various strategies, such as improving time management, seeking additional learning resources, joining academic communities, and securing scholarships or part-time jobs for those experiencing financial constraints. This research confirms that the alignment of a major with a student's interests significantly influences their academic success. Therefore, it is essential for the university to provide better guidance in major selection and offer enhanced academic support to help students adapt more easily and succeed in their studies.